EVALUATION OF THE ANTIBACTERIAL EFFECT OF THE ESSENTIAL OIL OF Juniperus communis ASSOCIATED WITH THE ANTIMICROBIAL GENTAMICIN AGAINST STRAINS OF Klebsiella pneumoniae (REMUNOM, 2025)
Patients in Intensive Care Units (ICUs) are susceptible to infections due to their compromised immune system. Oral changes are common during this period, which implies a greater risk of local, respiratory and opportunistic infections. Among the main causes of infections in hospital patients is Klebsiella pneumoniae, a gram-negative bacterium found in mucous membranes and resistant to a range of routinely used antimicrobials. From this perspective, complementary therapies have emerged as an alternative for combating multi-resistant bacteria, as is the case with essential oils from medicinal plants. The aim of this study was to evaluate the antibacterial effect of Juniperus communis essential oil associated with the antimicrobial gentamicin against strains of Klebsiella pneumoniae. The research was carried out using the solid medium diffusion technique. Filter paper disks containing the antimicrobial gentamicin were placed on Muller-Hinton Agar and inoculated with the bacterial suspension and soaked in the essential oil's MIC. For each of the strains chosen, a control study was carried out to correlate the inhibition halos formed. The study showed that the association had an indifferent and antagonistic effect on most of the strains investigated. However, effective responses were seen when the essential oil was combined with the antimicrobial against the KP 104 strain. The antimicrobial potential of the Juniperus communis species should be evaluated in new studies in order to understand this therapeutic property. Keywords: Anti-Bacterial Agents, Phytotherapy, Phytotherapy, Microbiology, Dentistry.